2022
DOI: 10.3390/biom12070860
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Cystatin C Has Prognostic Value in Peripheral Artery Disease

Abstract: Despite its association with adverse outcomes, peripheral artery disease (PAD) remains undertreated. Cystatin C is elevated in patients with renal disease and may be a marker of cardiovascular disease. We examined the prognostic ability of urinary Cystatin C (uCystatinC) in predicting adverse PAD-related events. In this prospective case-control study, urine samples were collected from patients with PAD (n = 121) and without PAD (n = 77). The cohort was followed for 2 years. uCystatinC was normalized to urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…ratio in healthy term neonates are similar than the values observed in the adult population. However, in stable preterm neonates, they are significantly higher than in healthy adults [29]. Our study found that the cystatin C/cr.…”
Section: Discussioncontrasting
confidence: 43%
“…ratio in healthy term neonates are similar than the values observed in the adult population. However, in stable preterm neonates, they are significantly higher than in healthy adults [29]. Our study found that the cystatin C/cr.…”
Section: Discussioncontrasting
confidence: 43%
“…This suggests that PAD patients with higher baseline levels of inflammation, as measured by AGP, are more likely to have limb-related complications over the long term. Our paper provides some evidence that AGP can be used as a potential prognostication biomarker for PAD, adding to our repository of potential biomarkers to improve prognosis of this condition via a multifaceted approach ( 7 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings were replicated in urinary FABP3 ( 8 , 9 ). More recently, we showed that higher levels of Cystatin C correlated with long-term adverse PAD-related events ( 10 ). These results suggest that there is potential to develop a multifaceted approach to risk stratifying PAD patients using a panel of biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary cystatin C is a marker classically associated with kidney function. However, the elevated urine cystatin C:urine creatinine ratio is associated with PAD and is a predictive of major adverse limb events [22]. During angiography, myeloperoxidase levels were assessed in patients with PAD and CAD.…”
Section: Prognostic Vitals and Lab Valuesmentioning
confidence: 99%